Ancient DNA, lipid biomarkers and palaeoecological evidence reveals construction and life on early medieval lake settlements - A. G. Brown (Nature Portfolio, 2021)
Abstract Direct evidence of ancient human occupation is typically established through archaeological excavation. Excavations are costly and destructive, and practically impossible in some lake and wetland environments. We present here an alternative approach, providing direct evidence from lake sediments using DNA metabarcoding, steroid lipid biomarkers (bile acids) and from traditional environmental analyses. Applied to an early Medieval Celtic settlement in Ireland (a crannog) this approach provides a site chronology and direct evidence of human occupation, crops, animal farming and on-site slaughtering. This is the first independently-dated, continuous molecular archive of human activity from an archeological site, demonstrating a link between animal husbandry, food resources, island use. These sites are under threat but are impossible to preserve in-situ so this approach can be used, with or without excavation, to produce a robust and full site chronology and provide direct evidence of occupation, the use of plants and animals, and activities such as butchery.